2013
DOI: 10.1038/emboj.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-controlled ubiquitination of the EGFR directs receptor fate

Abstract: How the cell converts graded signals into threshold-activated responses is a question of great biological relevance. Here, we uncover a nonlinear modality of epidermal growth factor receptor (EGFR)-activated signal transduction, by demonstrating that the ubiquitination of the EGFR at the PM is threshold controlled. The ubiquitination threshold is mechanistically determined by the cooperative recruitment of the E3 ligase Cbl, in complex with Grb2, to the EGFR. This, in turn, is dependent on the simultaneous pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
210
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(244 citation statements)
references
References 54 publications
20
210
1
Order By: Relevance
“…To obtain additional mechanistic insight into the function of PHD3 in EGFR internalization and to confirm that PHD3 acts as a scaffolding adaptor that regulates the early steps of EGFR endocytosis, we next analysed the role of PHD3 in the recruitment of known EGFR interactors that play a central part in EGFR internalization and signalling. Binding of the E3 ligase Cbl, in complex with Grb2, to phosphorylated EGFR has been shown to act as a switch that tightly regulates the ubiquitination of the receptor and can trigger its internalization 29 . Therefore, we first investigated whether the recruitment of Cbl and Grb2, as well as the ubiquitination levels of EGFR, were altered following PHD3 loss.…”
Section: Phd3 Interacts With Egfr and Regulates Its Internalizationmentioning
confidence: 99%
“…To obtain additional mechanistic insight into the function of PHD3 in EGFR internalization and to confirm that PHD3 acts as a scaffolding adaptor that regulates the early steps of EGFR endocytosis, we next analysed the role of PHD3 in the recruitment of known EGFR interactors that play a central part in EGFR internalization and signalling. Binding of the E3 ligase Cbl, in complex with Grb2, to phosphorylated EGFR has been shown to act as a switch that tightly regulates the ubiquitination of the receptor and can trigger its internalization 29 . Therefore, we first investigated whether the recruitment of Cbl and Grb2, as well as the ubiquitination levels of EGFR, were altered following PHD3 loss.…”
Section: Phd3 Interacts With Egfr and Regulates Its Internalizationmentioning
confidence: 99%
“…To accomplish this, we created a new site that takes into account the simultaneous phosphorylation states of Y1045 and Y1068 while still using our model reduction assumptions (see the electronic supplementary material). Using this extended model, we performed simulations to explore whether these assumptions could reproduce the cooperative behaviour in cCbl binding to EGFR observed [33]. Surprisingly, we found that there was no predicted difference in recruitment of Grb2 or cCbl as a function of EGF dose (figure 3c), despite the higher affinity of the Grb2-cCbl complex and the reliance on two sites to be simultaneously phosphorylated.…”
Section: Refining the Model For Analysis Of Grb2 -Ccbl Cooperativitymentioning
confidence: 98%
“…Although there are certainly some potential deviations from the assumptions in a strict sense, in many respects, we conclude that they may reasonably apply to the EGFR system. One significant deviation is the cooperative recruitment of the E3 ubiquitin ligase c-Cbl to the EGFR, depending on the presence of Grb2 [33]. The theory as developed above does not allow for such a possibility, but we derive a special case here that allows us to introduce this feature without considering the full array combinatorial complexity.…”
Section: Applying the Theory To Model Ligand-induced Epidermal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…concentrations, where as with higher concentrations of ligand, (10-100 ng/mL) the receptor undergoes Clathrin-independent endocytosis via caveolae [25,26].…”
Section: Sigismund Et Al Stimulated Receptor Activation With Egf Formentioning
confidence: 99%